El Big Data y su impacto en los financiamientos de comercio exterior de las pymes en el sector financiero peruano entre el 2011 y 2018 - Tapia Alva, Carlos José (2021)
Due to the appearance of Big Data and the new techniques associated with the treatment and analysis of large databases in business management, the enterprises could make quick decisions in a context of uncertainty. The present work aims to demonstrate the impact that this context had on SME Foreign Trade financing, based on a correlation between the implementation of Big Data in the Peruvian financial sector and the disbursements made during the 2011 and 2018 period. The disbursements of the most representative banks of this financial product are analyzed, as well as their evolution in the Market Share and the evolution of default. The results suggest that there is an impact that Big Data had on this type of financing.